Sistem Informasi Penjualan Berbasis Web pada UD Dwi Surya Aluminium dan Kaca Yogyakarta - Fanny Fatma Wati; Uswatun Khasanah (Paradigma, 2019)
At this time the development of information technology is growing very rapidly. Directly or indirectly affect various aspects of life, including the business world. Almost all aspects have used computers as a tool to provide convenience for companies. UD Dwi Surya Aluminum and Glass Yogyakarta need an information system that support and provide satisfactory service for the customer. For that the author tries to make Thesis web-based sales information system on UD Dwi Surya Aluminum and Glass which until now has not been computerized. Sales system running on the UD is still conventional and data processing inside the UD is still manual, such as recording payment transactions and making reports that are still recorded in a book. The data storage in the book is considered less effective because of the data search process that takes a long time and often error recording due to human error. And Marketing of goods made UD Dwi Surya Aluminum and Glass around the scope of Yogyakarta. The design of the sales information system in this UD uses the waterfall method. With this sales website is the best solution to solve existing problems in this company, as well as with this system can improve sales service, especially on product offerings and facilitate in processing sales data that exist in the UD. A computerized system is better than a manual system, a sales system that is now more conducive than the previous system.